Increased Oxidative Stress in Children with Post Infectious Bronchiolitis Obliterans - Mallol-Villablanca, E; Aguirre-Camposano, V; Espinosa-Ferrada, V (2011)
Background: There is increasing evidence that oxidative stress is involved in the development and severity of bronchiolitis obliterans occurring in post-transplant patients. In developing countries, the most common form of bronchiolitis obliterans occurs after severe lung infection, mainly caused by adenovirus. However, the oxidative status in the lungs of children with post infectious bronchiolitis obliterans is unknown. Methods: The aim of this study was to measure the oxidant (8-isoprostane and protein carbonyls) and antioxidant (catalase and glutathione peroxidase) activity in the bronchoalveolar lavage fluid of 21 children with post-infectious bronchiolitis obliterans, and to correlate oxidant/antioxidant level with lung function. Lung function was assessed by spirometry and plethysmography, one week prior to fiberbronchoscopy. Results: There was a markedly increased oxidative stress (lipid and protein oxidation) in the bronchoalveolar lavage fluid, and a notorious impairment of lung function demonstrating moderate-severe distal airway narrowing. There was not a significant correlation between the level of oxidants or antioxidants and lung function. There was a consistent antioxidants/oxidants pattern characterised by markedly increased 8-isoprostane and carbonyls, increased GPx and normal catalase activity. Conclusion: The present study shows for the first time that children with post-infectious bronchiolitis obliterans have a markedly increased oxidative stress in their lungs. © 2010 SEICAP.